Pengembangan Buku Matematika Berbasis Multiple Intelligences pada Sekolah Berdampak Merdeka Belajar Kampus Merdeka - Syafitri, Ely; Rahmadani, Elfira (Universitas Suryakancana, 2022)
The purpose of this research is to produce a math book based on multiple intelligences that meets the criteria of being valid, practical, and effective. The development model applied is the Plomp model, consisting of the initial research, development, and assessment phases. Data analysis of validity and practicality was carried out by converting quantitative data in the form of assessment scores into qualitative data on a scale of five. Effectiveness data analysis based on test results was carried out by determining the percentage of student learning completeness and for the results of questionnaires and attitude observations carried out by determining the percentage of students in each category. Based on the validation results, the developed math book has a valid category. The test results show that the developed math book has a practical and effective category. Mathematics books reached the very practical category for teacher assessment and the practical category for the results of observing the implementation of the learning process and student assessment. Mathematics books also achieved the effective category based on the results of the competency test and multiple intelligences questionnaire.